2022
DOI: 10.3389/fvets.2022.954675
|View full text |Cite
|
Sign up to set email alerts
|

Guanidine acetic acid exhibited greater growth performance in younger (13–30 kg) than in older (30–50 kg) lambs under high-concentrate feedlotting pattern

Abstract: Guanidine acetic acid (GAA) is increasingly considered as a nutritional growth promoter in monogastric animals. Whether or not such response would exist in rapid-growing lambs is unclear yet. The objective of this study was to investigate whether dietary supplementation with uncoated GAA (UGAA) and coated GAA (CGAA) could alter growth performance, nutrient digestion, serum metabolites, and antioxidant capacity in lambs. Seventy-two small-tailed Han lambs initially weighed 12 ± 1.6 kg were randomly allocated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
(44 reference statements)
1
8
0
Order By: Relevance
“…Meat color is related to oxidation state of pigment proteins. Although we had proved that GAA addition improved the antioxidant capacity [15]. The meat color was similar among the two forage types and the forms of GAA added, which was consistent with a recent s report in lamb [37].…”
Section: Meat Quality Traitssupporting
confidence: 92%
See 1 more Smart Citation
“…Meat color is related to oxidation state of pigment proteins. Although we had proved that GAA addition improved the antioxidant capacity [15]. The meat color was similar among the two forage types and the forms of GAA added, which was consistent with a recent s report in lamb [37].…”
Section: Meat Quality Traitssupporting
confidence: 92%
“…In ruminants, the administration of GAA (0.6 0.6 or 0.9 g/kg) has the potential to improve BW, ADG, and feed e ciency in Angus bulls [14]. We had con rmed elevated insulin-like growth factor1 (IGF-1) in serum with the addition of GAA [15]. However, the binding of IGF-1 and IGF-1 receptor can activate mammalian target of rapamycin (mTOR), a master protein kinase involved in cellular growth and protein synthesis [16].…”
Section: Introductionmentioning
confidence: 99%
“…In one of our previous studies, the application of GAA was confirmed to improve growth performance and apparent total tract nutrient digestibility in lamb feeding practice [ 33 ]. In the present study, GAA feeding resulted in higher total VFA assessed at two stages.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, at the phylum level, Firmicutes and Bacteroidota were the dominant phyla, which are known to be involved in carbohydrate and protein degradation [ 33 ]. The interaction between forage type and GAA addition was found to affect the abundance of Bacteroidota .…”
Section: Discussionmentioning
confidence: 99%
“…In bulls, it has been reported that GAA increases the microbial population and improves the rumen fermentation profile and nutrient digestibility without altering blood biochemistry parameters [8,24]. Meanwhile, in sheep, performance, carcass characteristics and meat nutritional content have been reported to improve in association with GAA [25,26]. Other studies reported that GAA in ruminants increased daily weight gain, feed conversion efficiency and total short-chain fatty acid (SCFA) production [27].…”
Section: Introductionmentioning
confidence: 99%